Reasons for belief - Reisner, Andrew Evan, 1975-; Steglich-Petersen, Asbjrn (Cambridge University Press, 2011)
"Philosophers have long been concerned about what we know and how we know it. Increasingly, however, a related question has gained prominence in philosophical discussion: what should we believe and why? This volume brings together twelve new essays that address different aspects of this question. The essays examine foundational questions about reasons for belief, and use new research on reasons for belief to address traditional epistemological concerns such as knowledge, justification and perceptually acquired beliefs. This book will be of interest to philosophers working on epistemology, theoretical reason, rationality, perception and ethics. It will also be of interest to cognitive scientists and psychologists who wish to gain deeper insight into normative questions about belief and knowledge"--